Exploring consumer responses to official endorsement: roles of credibility and attractiveness attributes in live streaming - Cheng, Guo; Li, Wenjie; He, Mingli; Liao, Luyuan (Frontiers in Psychology, 2024)
Distinct from celebrity, expertise, and peer endorsement, official endorsement represents a new paradigm in which local government officials promote local products and brands via online platforms, primarily live streaming. Employing the source credibility and source attractiveness model, we developed a framework incorporating official credibility and attractiveness as antecedents, with consumer perceived security and enjoyment as mediators, culminating in purchase intention and local brand awareness. Furthermore, we also take into account consumer region and power distance belief. The study garnered 594 responses from an online survey. The structural equation model results indicate that official credibility attributes (expertise, trustworthiness, and government credibility) elevate consumer perceived security, whereas official attractiveness attributes (physical attractiveness, interaction friendliness, and similarity with consumers) amplify consumer enjoyment. Both perceived security and enjoyment positively impact purchase intention and local brand awareness. Additionally, consumer region and power distance belief partially moderate these relationships. Theoretically, this study pioneers the exploration of official endorsement, expanding the endorsement literature. Practically, it provides crucial insights for marketing professionals and government officials on leveraging official endorsement for local products and brands.